A new model based on the in-plane deformation for the conformal piezoelectric systems for characterization of soft tissue modulus. (August 2022) - Zhao, Hongyu; Dagdeviren, Canan; Liu, Guodong; Cao, Peng; Wang, Jianru; Sha, Baolin; Wang, Guosheng; Cui, Jingqiang; Su, Yewang
Abstract: Mechanical assessment of the human skin is critically important for clinical diagnosis and treatment of disease. Past works developed a conformal piezoelectric system (CPS) that enables the noninvasive in vivo measurement of the elasticity modulus of the skin, and a mechanical model based on the mechanism of out-of-plane extension of the capacitor-type structures. Here, we present a new theoretical model that is established based on the mechanism of the in-plane deformation. The study on both the free-standing CPS and the CPS mounting to the polydimethylsiloxane (PDMS) target substrates verified the universality of the new model. The experimental and theoretical results consistently show that the output voltage of the first sensor approximately linearly increases with the increase of not only the applied voltage but also the modulus of the PDMS. The optimal usage mode of the CPS, in which the voltage is applied to all actuators simultaneously, is proposed for the measurement of the elastic modulus of target substrates such as skin.